The Personal computer - Time-Life Books (Alexandria, Va. : Time-Life Books, 1989)
Three essays discuss the development of the personal computer. Includes glossary, index, and bibliography.
Includes index.
Bibliography: p. 121-124.
Wilson's Public Library.
Wilson's Senior High School.
8.9
8.9
Keywords: Microcomputers; Personal computers